Caught in the Crossfire: Unravelling the complex interplay of exploitation and agency in children associated with Boko Haram - Achilli, Luigi (Anti-Trafficking Review, 2024)
This paper investigates the experiences of children associated with Boko Haram in Northeast Nigeria. The central argument posits that, within highly coercive environments, exploitation and agency are mutually constitutive. While acknowledging the prevalent exploitation of these children, it is crucial to recognise how such exploitation is intimately connected to their agency. As economic, social, and political pressures mount, children may perceive participation in Boko Haram (and self-exploitation) as the only viable means to achieve various goals—from protecting their families and communities to seeking self-significance. Consequently, exploitation—whether orchestrated by group leaders or members—may be consciously embraced by children as a means to create new horizons of possibilities. Simultaneously, by engaging in Boko Haram’s activities, children reproduce a system aimed to their own exploitation and vilification. Neglecting the complexities inherent in children’s associations with Boko Haram has potential implications for their reintegration and community healing processes.